2022
DOI: 10.1088/1402-4896/ac9863
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational analysis of Einstein-non-linear-Maxwell-Yukawa black hole under the effect of Newman-Janis algorithm

Abstract: In this paper, we analyze the rotating Einstein-non-linear-Maxwell-Yukawa black hole solution by Janis-Newman algorithmic rule and complex calculations. We investigate the basic properties (i.e., Hawking radiation) for the corresponding black hole solution. From the horizon structure of the black hole, we discuss the graphical behavior of Hawking temperature T H and analyze the effects of spin parameter (appears due to Newman-Janis approach) on the T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Zhang and Pradhan [43] investigated that how corrected entropy affected the Kerr-Newman-AdS and RN-AdS BHs, they found that there was a quadratic phase transition occurring because of the thermal fluctuations. Moreover, the thermodynamics of various types of BHs under the influence of correction parameter is analyzed, they checked the relation of other thermodynamics quantities with the corrected entropy and for stability reasons [44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Pradhan [43] investigated that how corrected entropy affected the Kerr-Newman-AdS and RN-AdS BHs, they found that there was a quadratic phase transition occurring because of the thermal fluctuations. Moreover, the thermodynamics of various types of BHs under the influence of correction parameter is analyzed, they checked the relation of other thermodynamics quantities with the corrected entropy and for stability reasons [44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%